Synthesis of Water-Soluble Cyclen-Functionalised Fullerene C60 Derivatives. (April 2014) - He, Jiaheng; Yan, Lipeng; Liu, Guoping; Ma, Zongping; Luo, Shunzhong; He, Songhua; Guo, Qiang; Lan, Jingbo; Wu, Di
The fullerene family has interesting photophysical, electrochemical and mechanical properties with applications in organic solar cells, nanotechnology, superconductivity, chemosensors and biomedicine. Water-soluble cyclen-functionalised fullerene derivatives cyclen-C60 -1 and bis(cyclen)-C60 -2 have been synthesised. The whole synthetic routes are simple and the total yields are relatively high.